Elevating the water/salt selectivity of polybenzimidazole to the empirical upper bound of desalting polymers by marrying N-substitution with chlorination. (18th November 2022) - Zhang, Chenchen; Chen, Si; Hu, Linan; You, Meng; Meng, Jianqiang
Abstract: Polybenzimidazole (PBI) was modified by marrying N-substitution with chlorination in order to improve its desalination properties. Based on the solution-diffusion theory, the effect of N-substitution and then chlorination on the water/salt transport properties of PBI was systematically analyzed. Although the introduction of hydrophobic p-toluenesulfonyl groups decreases water sorption, significantly increases water diffusion by weakening the hydrogen bonding between polymer chains. As a result, the water permeability of substituted PBI (SPBI) was 20 times higher than that of PBI. In terms of salt transport, the increase in salt diffusion of SPBI caused by the weaker inter-chain interactions was offset by a substantial decrease in salt sorption due to the combined effect of electrostatic repulsion and increased accessibility of hydrophilic groups to bind water, leading to equivalent salt permeability of PBI to SPBI. Controlled chlorination of SPBI under acidic conditions can further improve polymer water diffusion and thus water/salt diffusivity selectivity. The permeation of both SPBI and chlorinated SPBI is diffusion dependent. Therefore, combining N-substitution and chlorination is an effective strategy to simultaneously improve PBI permeability and water/salt selectivity for desalination applications. Graphical abstract: Image 1 Highlights: Combining N-substitution and chlorination improves water/salt selectivity of PBI. The effect of N-substitution on the chlorination mechanism of SPBI was elucidated. N-substitution can add water/salt sorption selectivity benefits. Controlled acidic chlorination further enhances diffusion selectivity of SPBI.